Kuwait's marine biodiversity: Qualitative assessment of indicator habitats and species. (February 2021) - Edmonds, N.J.; Al-Zaidan, A.S.; Al-Sabah, A.A.; Le Quesne, W.J.F.; Devlin, M.J.; Davison, P.I.; Lyons, B.P.
Abstract: The tropical waters of the Northern Arabian Gulf have a long history of maritime resource richness. High levels of biodiversity result from the complex matrix of coastal habitats, coral reefs and sea grass beds that characterise the region. Insight into the ongoing health of such habitats and the broader Kuwait maritime environment can be gauged by the status of indicator species found within these habitats. Here we review information on the occurrence, distribution and threats to key marine habitats and associated indicator species to provide an updated assessment of the state of the Kuwait's marine biodiversity. Critical evaluation of historic data highlights knowledge gaps needed inform the focus of future monitoring and conservation efforts. This assessment is designed to evaluate performance against environmental policy commitments, while providing a solid foundation for the design of comprehensive marine ecosystem management strategies. Highlights: Kuwait hosts a broad range of marine habitats that support high levels of regional biodiversity, including critically endangered marine species. The precise extent and condition of marine habitats, including coral reefs and seagrass meadows, have yet to be accurately mapped and fine-scale knowledge of biodiversity distribution/abundance is lacking. Kuwait's marine environment provides habitat for charismatic species such as cetaceans, breeding sea turtle populations and hosts a diverse range of internationally important breeding and migratory bird species. In the face of anthropogenic threats and an expanding human population there is a need to develop a baseline assessments, indices, and programmes to monitor biodiversity change to inform effective marine management. Threats to biodiversity are likely to be exacerbated by climate change. The Gulf is already characterised by high temperatures and salinities, close to the habitable limits of some organisms.